Enhanced Control of Cucumber Wilt Disease by Bacillus amyloliquefaciens SQR9 by Altering the Regulation of Its DegU Phosphorylation - Xu, Zhihui; Zhang, Ruifu; Wang, Dandan; Qiu, Meihua; Feng, Haichao; Zhang, Nan; Shen, Qirong (Applied and Environmental Microbiology, 2014)
Bacillus amyloliquefaciens strain SQR9, isolated from the cucumber rhizosphere, suppresses the growth of Fusarium oxysporum in the cucumber rhizosphere and protects the host plant from pathogen invasion through efficient root colonization. In the Gram-positive bacterium Bacillus , the response regulator DegU regulates genetic competence, swarming motility, biofilm formation, complex colony architecture, and protease production. In this study, we report that stepwise phosphorylation of DegU in B. amyloliquefaciens SQR9 can influence biocontrol activity by coordinating multicellular behavior and regulating the synthesis of antibiotics. Results from in vitro and in situ experiments and quantitative PCR (qPCR) studies demonstrate the following: (i) that the lowest level of phosphorylated DegU (DegU∼P) (the degQ mutation) impairs complex colony architecture, biofilm formation, colonization activities, and biocontrol efficiency of Fusarium wilt disease but increases the production of macrolactin and bacillaene, and (ii) that increasing the level of DegU∼P by degQ and degSU overexpression significantly improves complex colony architecture, biofilm formation, colonization activities, production of the antibiotics bacillomycin D and difficidin, and efficiency of biocontrol of Fusarium wilt disease. The results offer a new strategy to enhance the biocontrol efficacy of Bacillus amyloliquefaciens SQR9.